Kay G. answered • 03/17/14

Tutor

4.9
(34)
~20 Years Accounting Tutoring Experience

It doesn't jive because it's not a solution for that equation. -4 * 2 is indeed -8. Positive times negative equals negative. (It's not about the 2 specifically - it's just about one positive and one negative = negative.)

You did nothing wrong.

x = 0 is the y intercept. If you plug in just the 0 for x, and solve, you'll find that y = -2.

Why do you think this point works? What was the actual question being asked?

Kay G.

That answer is incorrect. I'm not sure what method you're learning, but I'll do elimination:

First rearrange 2y = 2x - 4 to standard form:

Subtract 2x from both sides:

2y - 2x = 2x - 2x - 4

2y - 2x = -4

Then just turn the x and y terms around (don't forget the - sign is on the x one, and an understood + on the y one):

-2x + 2y = -4

So now we have:

3x - 4y = 8

-2x + 2y = -4

Multiply the 2nd one through by 2:

(2)(-2x + 2y) = -4(2)

-4x + 4y = -8

So we now have:

3x - 4y = 8

-4x + 4y = -8

--------------------

-x = 0

(You can actually ignore the - sign on that, but just to prove it, you can multiply both sides by -1 and of course you'll still have 0.)

Plug back in to either original equation, but I'll do both:

3(0) - 4y = 8

- 4y = 8 --> divide both sides by -4

y = -2 (not positive)

2y = 2(0) - 4

2y = -4 --> divide both sides by 2

y = -2

I even ran the whole thing through a second time from scratch, just to make sure I didn't make some silly mistake. And the positive 2 wasn't working for you either.

Report

03/18/14

Karen L.

03/18/14